2020
DOI: 10.1002/er.6058
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and application of sulfonated polysulfone in an electrochemical hydrogen storage system

Abstract: Summary Storage of hydrogen in/on solid‐state materials is predicted from their tendency to adsorb‐desorb hydrogen. It is crucial to find a new class of materials that can reversibly store hydrogen at high rates under reasonable temperature, pressure, and cost conditions. Polymeric materials have recently come to the fore of hydrogen storage technologies because of their reversible capacity, approximately high surface area, and thermomechanical stabilities. Here, we report, for the first time, a polymer for hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…This study provides a novel concept for the fabrication of polymers and is important for the development of conductive polymers. Salehabadi et al 272 applied a low-cost sulfonated polymer in the field of electrochemical hydrogen storage for the first time. It was found that the sulfonated polysulfone (SPSU) exhibited a maximum discharge capacity of 500 mAh g −1 and a hydrogen storage capacity of 1.8 wt %.…”
Section: Carbonaceous Materialsmentioning
confidence: 99%
“…This study provides a novel concept for the fabrication of polymers and is important for the development of conductive polymers. Salehabadi et al 272 applied a low-cost sulfonated polymer in the field of electrochemical hydrogen storage for the first time. It was found that the sulfonated polysulfone (SPSU) exhibited a maximum discharge capacity of 500 mAh g −1 and a hydrogen storage capacity of 1.8 wt %.…”
Section: Carbonaceous Materialsmentioning
confidence: 99%
“…For example, polysulfone has been introduced in the fabrication of AEM components for alkaline electrolyzer system. As an organic polymer, polysulfone is commonly used in electrochemical applications as a fuel barrier on all sides due to the high durability of the chemical and thermal properties 75,76 . Parrondo et al 77 utilized polysulfone to fabricate the alkaline solid polymer membrane to apply AEM electrolyzer.…”
Section: Progress Of Polymeric Materials As An Alkaline Solid Polymeric Membrane In Aem Electrolyzermentioning
confidence: 99%
“…while the incorporation of polysulfone (PS) polymer improves the composite's mechanical strength and structural stability [6]. while polysulfone (PS) is added to improve mechanical strength and structural stability [7].…”
Section: Introductionmentioning
confidence: 99%